2012
DOI: 10.1111/j.1742-4658.2012.08535.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the selectivity of protein phosphatase 1 for pharmacological intervention

Abstract: Selective and reversible phosphorylation is one of the most common post-translational modifications of proteins. Although kinase inhibitors are popular in drug development programmes, selective pharmacological manipulation of phosphatase activity has been challenging to achieve. We review recent advances in the development of selective inhibitors of dephosphorylation events and discuss the potential applications of small-molecule phosphatase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…GBZ was recently identified as an inhibitor of stressinduced dephosphorylation of eIF2α by its ability to inhibit the activity of eIF2α phosphatase GADD34, resulting in the accumulation of phospho-eIF2α. 43,44 Our results demonstrated that both T3 and GBZ induce eIF2α phosphorylation ( Fig. 2A and 6A and B).…”
Section: T3mentioning
confidence: 74%
“…GBZ was recently identified as an inhibitor of stressinduced dephosphorylation of eIF2α by its ability to inhibit the activity of eIF2α phosphatase GADD34, resulting in the accumulation of phospho-eIF2α. 43,44 Our results demonstrated that both T3 and GBZ induce eIF2α phosphorylation ( Fig. 2A and 6A and B).…”
Section: T3mentioning
confidence: 74%
“…PP1A however, in all its complexity, acting as a molecule associated with both pro-apoptotic and pro-tumorigenic roles [6][7][8], has come to light only recently in GBM, with our previous demonstration of PP1A as a novel connecting molecule in GBMs in the p53 subnetwork [2]. Further the recent literature on specificity of nuclear PP1A expression in GBMs [2] and its potential as a targetable molecule [18][19][20] made it imperative for us to understand the prognostic relevance of this molecule in GBM.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were observed in P. falciparum cultures treated with DHA followed by magnetic column purification to remove parasites unaffected by DHA (Figure 1B) (Teuscher et al, 2010). High levels of Plasmodium eIF2α phosphorylation in the small population (<1%, Figure S2) of latent parasites induced by ART were maintained with salubrinal (Sal) treatment, which has been established to inhibit the dephosphorylation of eIF2α in multiple species, including apicomplexan parasites (Tsaytler and Bertolotti, 2013; Zhang et al, 2010) (Figure 1C). Addition of Sal to the latent parasites delayed parasite recrudescence in a dose-dependent manner (Figures 1D, 1E and S2).…”
Section: Resultsmentioning
confidence: 99%